Graphene oxides prepared by Hummers’, Hofmann’s, and Staudenmaier’s methods : dramatic influences on heavy-metal-ion adsorption - Webster, Richard D. (2014)
Graphene oxide (GO), an up-and-coming material rich in oxygenated groups, shows much promise in pollution management. GO is synthesised using several synthetic routes, and the adsorption behaviour of GO is investigated to establish its ability to remove the heavy-metal pollutants of lead and cadmium ions. The GO is synthesised by Hummers’ (HU), Hofmann’s (HO) and Staudenmaier’s (ST) methodologies. Characterisation of GO is performed before and after adsorption experiments to investigate the structure–function relationship by using Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy. Scanning electron microscopy coupled with elemental detection spectroscopy is used to investigate morphological changes and heavy-metal content in the adsorbed GO. The filtrate, collected after adsorption, is analysed by inductively coupled plasma mass spectrometry, through which the efficiency and adsorption capacity of each GO for heavy-metal-ion removal is obtained. Spectroscopic analysis and characterisation reveal that the three types of GO have different compositions of oxygenated carbon functionalities. The trend in the affinity towards both PbII and CdII is HU GO>HO GO>ST GO. A direct correlation between the number of carboxyl groups present and the amount of heavy-metal ions adsorbed is established. The highest efficiency and highest adsorption capacity of heavy-metal ions is achieved with HU, in which the relative abundance of carboxyl groups is highest. The embedded systematic study reveals that carboxyl groups are the principal functionality responsible for heavy-metal-ion removal in GO. The choice of synthesis methodology for GO has a profound influence on heavy-metal-ion adsorption. A further enrichment of the carboxyl groups in GO will serve to enhance the role of GO as an adsorbent for environmental clean-up.